The Impact of Online PD Programs on Reflective Thinking Levels of Secondary EFL Teachers - Ade Mahmud; Tatu Zakiyatun Nufus (Universitas Majalengka, 2026)
This study investigates the impact of online professional development (PD) programs on the reflective thinking levels of secondary EFL teachers in Indonesia. Despite having sufficient content knowledge, many EFL teachers lack confidence in using English in classroom settings. Reflective practice has been identified as a key strategy to improve both language proficiency and professional confidence. This research, employing a case study design, focused on a 10-week online PD program organized by a university educator in Indonesia. A purposive sample of 10 EFL teachers participated in semi-structured interviews to explore their engagement in reflective practices. The findings indicate that while some teachers struggled to participate in reflective activities due to overwhelming workloads, others engaged in reflection-on-action and reflection-for-action. These reflections addressed areas such as instructional strategies, course organization, classroom management, student motivation and readiness, teaching materials, teaching awareness, and self-efficacy in teaching English language skills. However, reflection-in-action was notably absent. The results underscore the critical role of structured guidance and support within professional development (PD) programs in fostering meaningful reflective practices among secondary EFL teachers and the need for PD facilitators to prioritize incorporating reflective components into program design, ensuring that teachers are equipped with clear frameworks and tools for reflection.